Multiplex Assay for Quantification of Acute Phase Proteins and Immunoglobulin A in Dried Blood Spots - Vidova, Veronika; Stuchlikova, Eliska; Vrbova, Marketa; Almasi, Martina; Klanova, Jana; Thon, Vojtech; Spacil, Zdenek (Journal of proteome research, 2019)
Inflammation is the first line defense mechanism against infection, tissue damage, or cancer development. However, inappropriate inflammatory response may also trigger diseases. The quantification of inflammatory proteins is essential to distinguish between harmful and beneficial immune response. Currently used immunoanalytical assays may suffer specificity issues due to antigen-antibody interaction and possible cross-reactivity of antibody with other protein species. In addition, immunoanalytical assays typically require invasive blood sampling and additional logistics; they are relatively costly and highly challenging to multiplex. We present a multiplex assay based on selected reaction monitoring (SRM) for quantification of seven acute-phase proteins (i.e., SAA1, SAA2-isoform1, SAA4, CRP, A1AT-isoform1, A1AG1, A1AG2) and the adaptive immunity effector IGHA1 in dried blood spots. This type of sample is readily available from all human subjects including newborns. The study utilizes proteotypic isotopically labeled peptides with trypsin-cleavable tag and presents optimized and reproducible workflow and several important practical remarks regarding quantitative SRM assays development. The panel of inflammatory proteins was quantified with sequence specificity capable to differentiate protein isoforms with intra- and interday precision (<16.4% coefficient of variation (CV) and <14.3% CV, respectively). Quantitative results were correlated with immuno-nephelometric assay (typically greater than 0.9 Pearson's R).
Keywords: targeted quantitative proteomics; proteiny akutní fáze; imunita; Biomarkers; imunoglobulin A; biotest; dried blood spots; Immunity; zánět; Immunoglobulin A; immune response; Proteomics; Inflammation; test suché kapky krve; proteomika; selected reaction monitoring; Biological Assay; lidé; biologické markery; acute phase proteins; Dried Blood Spot Testing; Humans; Acute-Phase Proteins; inflammation markers